Africa as a living laboratory : empire, development, and the problem of scientific knowledge, 1870-1950 - Tilley, Helen, 1968- (Chicago : University of Chicago Press, 2011)
"Tropical Africa was one of the last regions of the world to experience formal European colonialism, a process that coincided with the advent of a range of new scientific specialties and research methods. Africa as a Living Laboratory is a far-reaching study of the thorny relationship between imperialism and the role of scientific expertise--environmental, medical, racial, and anthropological--in the colonization of British Africa. A key source for Helen Tilley's analysis is the African Research Survey, a project undertaken in the 1930s to explore how modern science was being applied to African problems. This project both embraced and recommended an interdisciplinary approach to research on Africa that, Tilley argues, underscored the heterogeneity of African environments and the interrelations among the problems being studied. While the aim of British colonialists was unquestionably to transform and modernize Africa, their efforts, Tilley contends, were often unexpectedly subverted by scientific concerns with the local and vernacular. Meticulously researched and gracefully argued, Africa as a Living Laboratory transforms our understanding of imperial history, colonial development, and the role science played in both"
An imperial laboratory : scientific societies, geopolitics, and territorial acquisitions -- A development laboratory : the African Research Survey, the machinery of knowledge, and imperial coordination -- An environmental laboratory : "native" agriculture, tropical infertility, and ecological models of development -- A medical laboratory : infectious diseases, ecological methods, and modernization -- A racial laboratory : imperial politics, race prejudice, and mental capacity -- An anthropological laboratory : ethnographic research, imperial administration and magical knowledge -- A living laboratory : ethnosciences, field sciences, and the problem of epistemic pluralism
Includes bibliographical references and index
Description based on print version record
eBooks on EBSCOhost
Keywords: African Research Survey; African Research Survey; African Research Survey; Großbritannien -- Consulate; Research -- Africa -- History -- 20th century; Research -- Africa -- History -- 21st century; Imperialism and science -- Africa -- History -- 20th century; Imperialism and science -- Africa -- History -- 21st century; Africa -- Research -- History -- 20th century; Africa -- Research -- History -- 21st century; Africa -- Colonization -- History -- 20th century; Africa -- Colonization -- History -- 21st century; Great Britain -- Colonies -- Africa -- History -- 20th century; Great Britain -- Colonies -- Africa -- History -- 21st century; Africa; History; Science; Electronic books; Biomedical Research -- history; Colonialism -- history; History, 20th Century; History, 21st Century; Africa; United Kingdom; History; Science; Impérialisme et sciences -- Afrique -- Histoire -- 20e siècle.; Impérialisme et sciences -- Afrique -- Histoire -- 21e siècle.; Afrique -- Recherche -- Histoire -- 20e siècle.; Afrique -- Recherche -- Histoire -- 21e siècle.; Grande-Bretagne -- Colonies -- Afrique -- Histoire -- 20e siècle.; Grande-Bretagne -- Colonies -- Afrique -- Histoire -- 21e siècle.; Médecine -- Histoire -- 20e siècle.; Médecine -- Histoire -- 21e siècle.; Afrique; Histoire; Sciences; Livres numériques.; history (discipline); science (modern discipline); e-books.; SCIENCE -- History; Science; British colonies; Colonization; Imperialism and science; Research; Africa; Forschung; Naturwissenschaften; Imperialismus; Kolonialismus; Kolonie; Afrika; Imperialism; Anthropological aspects; Agricultural development; Eugenics; Racial theories; Ecological aspects